A worldwide systematic review, meta‐analysis, and health risk assessment study of mycotoxins in beers. Issue 6 (19th October 2021) - Schabo, Danieli C.; Alvarenga, Verônica O.; Schaffner, Donald W.; Magnani, Marciane
Abstract : Abstract: Mycotoxins, including aflatoxins (AFs), ochratoxin A (OTA), deoxynivalenol (DON), fumonisins (FBs), and zearalenone (ZEN), have been reported as beer contaminants. This systematic review and meta‐analysis provide the prevalence and concentration of mycotoxins in beers and their worldwide distribution. Mycotoxin's exposure and cancer risk through beer consumption were determined. The overall pooled prevalence of mycotoxins in beers was 31% (95% confidence interval [CI] = 28%–35%; I 2  = 90%, p  = .00). The most prevalent mycotoxins in beers were DON and its derivatives (53%), OTA (52%), FBs (47%), followed by AFs (12%). Iran (99%), Hungary (95%), Denmark (92%), Armenia (83%), and Cyprus (83%) had the highest mycotoxin prevalence in beers. The global mycotoxins average concentration in beers was 12.52 μg/L (95% CI = 10.70–14.75 μg/L; I 2  = 100%, p  = .00). DON and its derivatives showed the highest concentration (26.91 μg/L), followed by FBs (23.19 μg/L), ZEN and its derivatives (20.25 μg/L), and AFs (15.65 μg/L). African region had the highest mycotoxins concentration (73.95 μg/L) mostly due to the high levels reported in beers from Cameroon (293.02 μg/L), Malawi (132.34 μg/L), and Eastern Cape province (126.12 μg/L). The meta‐regression indicated stability ( p ≥ .05) of the global pooled concentration of mycotoxins in beers over the years, whereas FBs concentration increased. The intake of DON and its derivatives, FBs, ZEN and its derivatives, and OTA through beers is of concern in African countries. OTA is also of concern in Brazil and Belgium. Results show high mycotoxins concentration in beers worldwide and highlight the health risks through contaminated beer consumption.